2012
DOI: 10.1080/1573062x.2011.630093
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the relationship between water main breaks and temperature covariates

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 6 publications
1
38
0
1
Order By: Relevance
“…The DI pipe average age of 16 years was recorded versus 22 years for CI pipe. Folkman [33] and Rajani et al [34] reported similar findings in other networks in the Greater Toronto. This finding is due to the nature of the soil around the pipes that triggers the pipe corrosion that mainly affects DI pipes leading to pitting and hole failures.…”
Section: Pipe Failures In Greater Toronto Areasupporting
confidence: 70%
See 4 more Smart Citations
“…The DI pipe average age of 16 years was recorded versus 22 years for CI pipe. Folkman [33] and Rajani et al [34] reported similar findings in other networks in the Greater Toronto. This finding is due to the nature of the soil around the pipes that triggers the pipe corrosion that mainly affects DI pipes leading to pitting and hole failures.…”
Section: Pipe Failures In Greater Toronto Areasupporting
confidence: 70%
“…This finding is due to the nature of the soil around the pipes that triggers the pipe corrosion that mainly affects DI pipes leading to pitting and hole failures. This average age at the first recorded failure implies that the soil has moderate corrosion [34]. Figure 6 also shows that the average time between subsequent failures for CI is 2.5 years, which is relatively larger than that of 1 year for DI.…”
Section: Pipe Failures In Greater Toronto Areamentioning
confidence: 86%
See 3 more Smart Citations